Answer:
The answers are
x
=
−
2
and
x
=
−
4
.
Explanation:
To start, the quadratic formula is
x
=
−
b
±
√
b
2
−
4
a
c
2
a
In this problem,
a
=
1
(as the
x
2
term has no coefficient),
b
=
6
, and
c
=
8
.
Plug those values into the quadratic equation to get:
x
=
−
6
±
√
6
2
−
4
(
1
)
(
8
)
2
(
1
)
Multiply
2
⋅
1
on the bottom of the fraction:
x
=
−
6
±
√
6
2
−
4
(
1
)
(
8
)
2
Square
6
and multiply
4
⋅
1
⋅
8
within the square root:
x
=
−
6
±
√
36
−
32
2
Subtract
36
−
32
inside the root:
x
=
−
6
±
√
4
2
Solve for
√
4
x
=
−
6
±
2
2
If the
±
is positive, you get
x
=
−
6
+
2
2
, which simplifies to
x
=
−
4
2
, or
−
2
If the
±
is negative, you get
x
=
−
6
−
2
2
, which simplifies to
x
=
−
8
2
, or
−
4